2015
DOI: 10.1093/mnras/stv008
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental parameters of the close interacting binary HD 170582 and its luminous accretion disc

Abstract: We present a spectroscopic and photometric study of the Double Period Variable HD 170582. Based on the study of the ASAS V-band light curve we determine an improved orbital period of 16.87177 ± 0.02084 days and a long period of 587 days. We disentangled the light curve into an orbital part, determining ephemerides and revealing orbital ellipsoidal variability with unequal maxima, and a long cycle, showing quasi-sinusoidal changes with amplitude ∆V= 0.1 mag. Assuming synchronous rotation for the cool stellar co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The temperature of the disk matches the temperature of the gainer on its inner edge and decreases with a radial profile described by an exponent a T . The model has been described in several papers, such as Mennickent & Djurašević (2013), Mennickent et al (2015), Mennickent (2019), where more details can be found.…”
Section: Light Curve Modelmentioning
confidence: 99%
“…The temperature of the disk matches the temperature of the gainer on its inner edge and decreases with a radial profile described by an exponent a T . The model has been described in several papers, such as Mennickent & Djurašević (2013), Mennickent et al (2015), Mennickent (2019), where more details can be found.…”
Section: Light Curve Modelmentioning
confidence: 99%
“…The stellar parameters used in this paper to find the best evolutionary model for HD 170582. Data are from Mennickent et al (2015). quantity value quantity value…”
Section: Doppler Tomographymentioning
confidence: 99%
“…It was recently studied by Mennickent et al (2015), who found a slightly evolved B-type star surrounded by a luminous accretion disc fed by a Roche-lobe overflowing Atype giant. Here we extend their analysis presenting new spectroscopic data and studying the Balmer emission lines.…”
mentioning
confidence: 99%
“…These DPV stars have also been observed as spectroscopic binaries (e.g. Mennickent et al 2005;Mennickent et al 2012;Mennickent et al 2015;Barría et al 2014), showing that they consist of an early B-type main sequence star and a hot, lower-mass, but evolved companion (i.e. an Algol-like system).…”
Section: Introductionmentioning
confidence: 91%
“…Finally, the mechanism producing the longer period in the DPV systems is also found in BeXRBs. Mennickent et al (2015) show a schematic of a DPV depicting the locations of a hot spot and bright spot on the Be star disc. The precession of the bright spot on the disc is equivalent to the precession of a density wave that produces the super-orbital periods in BeXRBs.…”
Section: The Link To Dpvsmentioning
confidence: 99%